2022
DOI: 10.3390/antiox11061046
|View full text |Cite
|
Sign up to set email alerts
|

5-Methyltetrahydrofolate Attenuates Oxidative Stress and Improves Kidney Function in Acute Kidney Injury through Activation of Nrf2 and Antioxidant Defense

Abstract: Oxidative stress is a major mediator of adverse outcomes in acute kidney injury (AKI). Deficiency of micronutrients, such as folate, is common in AKI. Our previous study reported that AKI impaired kidney reabsorption of folate and decreased plasma folate level in rats. The present study investigated the effect of 5-methyltetrahydrofolate (5-MTHF), a biologically active form of folate/folic acid, on AKI-impaired kidney function and oxidative stress. Sprague-Dawley rats developed AKI after kidney ischemia (45 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Firstly, folate may have beneficial effects on physical function through its antioxidant effect [ 41 , 42 ]. Several studies have shown that folate or folic acid supplementation may attenuate oxidative stress by improving biomarkers in the antioxidative defense system, such as increased serum total antioxidant capacity and glutathione (GSH) concentration [ 13 , 43 , 44 , 45 , 46 ]. Studies have found that oxidative stress is an independent predictor of functional disability [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, folate may have beneficial effects on physical function through its antioxidant effect [ 41 , 42 ]. Several studies have shown that folate or folic acid supplementation may attenuate oxidative stress by improving biomarkers in the antioxidative defense system, such as increased serum total antioxidant capacity and glutathione (GSH) concentration [ 13 , 43 , 44 , 45 , 46 ]. Studies have found that oxidative stress is an independent predictor of functional disability [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of 5-MTHF in several diseases has been studied in animal models. It has been shown that 5-MTHF administered intravenously in rats with acute kidney injury reduced oxidative stress by increasing glutathione concentrations and reducing renal lipid peroxidation [113]. Rats with developed aortic atherosclerosis treated with 5-MTHF showed a decrease in homocysteine levels, an improvement in the serum lipid profile, an increase in the expression of NO and NOS, an enhancement of the antioxidant properties of GSH activity and a decrease in the expression of inflammatory factors: TNF-α, IL-6, IL -1β and endothelial cell damage factors: ET-1 and sICAM-1.…”
Section: Folic Acid Versus 5-mthf In Cad Therapymentioning
confidence: 99%
“…Tumor necrosis factor alpha (TNF-α) is a conventional marker of tissue inflammation [ 6 ]. Important indicators of oxidative stress are the extracellular antioxidant enzyme glutathione peroxidase 3 (GPx3), the cellular antioxidant enzyme heme oxygenase 1 (HO-1), and its transcriptional regulator nuclear factor erythroid 2-related factor 2 (NRF2) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%